STRATEGI PERTAHANAN WILAYAH PULAU TERLUAR INDONESIA TERHADAP MALAYSIA (KASUS PULAU JEMUR DI PROVINSI RIAU) - Desriani "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Indonesia is an archipelago with the most numerous islands with their resources,including the ones owned in its outmost island. The Jemur Island are outmost island Indonesia.Island The outmost islands are rich in various resources but have not been managed yet. Thoseislands are also the first guard which acts as safeguard for the unity of Indonesia. Unfortunately,the government has not paid a comprehensive concern to those islands. It will endanger theentirety of Indonesia and caused great lost economically. Jemur Island is actually consists ofseveral clusters of island like: Tekong Emas island, Tekong Simbang island, Labuhan Bilikisland and some other small island. There is a probability that this island be a tourist window forof Riau in the future.This research focuses on Indonesia defenses strategy region outmost island to Malaysiain case Jemur Island the Province of Riau. Its strategic geographical location, in the middle ofIndonesia and Malaysia also gives this island an additional value to be developed in to a tourismresort. This research shows how Indonesia defense strategy region outmost island to Malaysia incase The Jemur Island with can strategy safety belt and potential border territory. And than theresearch also to explain potential Jemur Island to Indonesia, potential Jemur Island of Indonesiato Malaysia and analyzing conflict Jemur Island between Indonesia and Malaysia. Therefore, bythe way of good protection and management of the outmost islands, the unity of Indonesia will bedefended and the welfare of Indonesian will be enhanced. Data of this research collected frombooks, journals, working paper, government publications, newspaper, and searching frominternet.Keyword: Jemur Island, Border territory,The outmost Island, and Safety belt.